Olink proteomics reveals TNFRSF9 as a biomarker for abdominal aortic aneurysms - Runze Chang; Heng Wang; Chuanlong Lu; Jinshan Chen; Yaling Li; Maolin Qiao; Siqi Gao; Lizheng Li; Keyi Fan; Ruijing Zhang; Honglin Dong (iScience)
Summary: Abdominal aortic aneurysm (AAA) is a serious cardiovascular disease associated with chronic inflammation. The purpose of this study was to use the Olink proteomics to reveal serum inflammatory markers in AAA. We examined the expression levels of 92 inflammation-related proteins in patients with AAA (n = 18) and healthy individuals (n = 10) using the Olink proximity extension assay (PEA) inflammatory plate. Olink proteomics identified 38 differential proteins. Combined analysis of Olink proteomics and GSE183464 showed interleukin-6 (IL-6) and tumor necrosis factor receptor superfamily member 9 (TNFRSF9) were upregulated at both gene and protein levels in AAA patients. The ELISA results were consistent with the Olink proteomics results, and the receiver operating characteristic (ROC) curve analysis revealed that the binding of TNFRSF9 and IL-6 has high diagnostic value (Olink AUC = 0.9056; ELISA AUC = 0.950). Subsequently, elevated TNFRSF9 expression in AAA was confirmed by animal models, suggesting that TNFRSF9 may serve as a potential biomarker for AAA.